2018
DOI: 10.1103/physreve.97.012703
|View full text |Cite
|
Sign up to set email alerts
|

Ordering transitions of weakly anisotropic hard rods in narrow slitlike pores

Abstract: The effect of strong confinement on the positional and orientational ordering is examined in a system of hard rectangular rods with length L and diameter D (L>D) using the Parsons-Lee modification of the second virial density-functional theory. The rods are nonmesogenic (L/D<3) and confined between two parallel hard walls, where the width of the pore (H) is chosen in such a way that both planar (particle's long axis parallel to the walls) and homeotropic (particle's long axis perpendicular to the walls) orderi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(26 citation statements)
references
References 48 publications
3
23
0
Order By: Relevance
“…We studied the confined hard rod particles with a rectangular cross-section and edge lengths L, D, and D into a slit-like pore with flat and parallel hard walls where the walls are perpendicular to the z-axis and placed at = 0 and = and spread in the plane. We use the Onsager theory with the Parsons-Lee modification [27,52] within three-state Zwanzig approximation [53], which the orientation freedoms of the particles are along the x, y, and z directions. Therefore, the local density of each direction ( where = , , ) is a function of the z-coordinate only, and we can achieve the packing fraction () from the local densities ( ( ), = , and ) as below:…”
Section: Theorymentioning
confidence: 99%
See 2 more Smart Citations
“…We studied the confined hard rod particles with a rectangular cross-section and edge lengths L, D, and D into a slit-like pore with flat and parallel hard walls where the walls are perpendicular to the z-axis and placed at = 0 and = and spread in the plane. We use the Onsager theory with the Parsons-Lee modification [27,52] within three-state Zwanzig approximation [53], which the orientation freedoms of the particles are along the x, y, and z directions. Therefore, the local density of each direction ( where = , , ) is a function of the z-coordinate only, and we can achieve the packing fraction () from the local densities ( ( ), = , and ) as below:…”
Section: Theorymentioning
confidence: 99%
“…The nematic planar phase confined between two walls could be uniaxial (U) or biaxial (B). The U-B transition induced by a substrate(s) has been predicted to be second order for confined hard rod-like [27][28][29][30] and plate-like [31] particles. The biaxial nematic phases have been studied widely experimentally [32][33][34] and theoretically [35][36][37] due to their fast response time to the applied electric field, which is an essential factor in display technologies [38].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The density profiles showed planar ordering and damped oscillatory behavior [35]. For non-mesogenic particles with small aspect ratios (ε < 3) in the extreme confinement limit -small distances between the walls (h/d ≤ 2), a structural transition from a planar (particle's long axis parallel to the walls) to a homeotropic (particle's long axis perpendicular to the walls) layer with increasing density was observed [37]. For hard discorectangles between the two parallel walls in strongly confined systems (1 < h/d ≤ 2), a rich phase behavior with dependence on the value of the particles' aspect ratio has been observed [38].…”
Section: Introductionmentioning
confidence: 95%
“…It was shown that confined particles tend to align their long axes parallel to the confining walls with the effects being more pronounced for smaller separations between those walls. Strongly confined systems between two parallel walls have been examined, theoretically, for rectangular particles [35][36][37]. The density profiles showed planar ordering and damped oscillatory behavior [35].…”
Section: Introductionmentioning
confidence: 99%